(untitled) (Journal of Laboratory Animal Science, 2019)
Laboratory rodent colonies are commonly infested with pinworms namely Syphacia obvelata and Syphacia muris, often results in clinical signs such as diarrhea and rectal prolapse in heavy infestation. The pinworm infestation in rodents affects the experimental observations and hence it is important to eradicate them from the colony. Division of Laboratory Animals at Sree Chitra Tirunal Institute for Medical Sciences and Technology (SCTIMST) maintains rats and mice colonies. Pinworm ova were determined by perianal impression with cellophane tape testing (CTT) under low power of a compound microscope. The mice and rats were divided into 2 groups with 10 males and 10 females in each group. Group I was treated with piperazine (10.8 mg/ml of drinking water) for a period of 28 days and group II was treated with piperazine (10.8 mg/ml) for a period of 14 days followed by ivermectin (0.01mg/ml) for 14 days. Cages and accessory equipments were disinfected with activated gluteraldehyde, 2.45% w/v. All supplies including bedding and accessories were autoclaved at 121oC temperature, 15 lb pressure for 20 minutes. The present study revealed that the parasites were eradicated from those groups treated with combination drug (piperazine and ivermectin) therapy while the group treated with piperazine alone could not demonstrate a complete eradication. The two drug (piperazine and ivermectin) regime over a 4-week period, associated with appropriate sanitation programme was found to be effective in eradication of pin worms in laboratory rodents.